#### Answer

3

#### Work Step by Step

$\frac{x}{2}$ =$\frac{x}{3}$+$\frac{1}{2}$
subtract $\frac{x}{3}$ from both sides
$\frac{x}{2}$ -$\frac{x}{3}$ =$\frac{x}{3}$+$\frac{1}{2}$ -$\frac{x}{3}$
$\frac{x}{2}$ -$\frac{x}{3}$=$\frac{1}{2}$ LCD is 6
$\frac{x}{2}$ $\times$$\frac{3}{3}$ - $\frac{x}{3}$$\times$$\frac{2}{2}$=$\frac{1}{2}$$\times$$\frac{3}{3}$
$\frac{3x}{6}$ -$\frac{2x}{6}$ =$\frac{3}{6}$
$\frac{3x-2x}{6}$ =$\frac{3}{6}$
$\frac{x}{6}$=$\frac{3}{6}$
x=3
The solution is 3
check
$\frac{x}{2}$ =$\frac{x}{3}$+$\frac{1}{2}$
$\frac{3}{2}$ =$\frac{3}{3}$+$\frac{1}{2}$
1$\frac{1}{2}$=1+$\frac{1}{2}$
1$\frac{1}{2}$=1$\frac{1}{2}$